Expression of Mesothelial Marker Calretinin in Breast Cancer - Aboobacker, Dr. Kalathingal Kamarunisha; Saldanha, Dr. Prema (International Journal of Innovative Research in Medical Science, 2019)
Calretinin (CR) is a calcium binding protein of calmodulin superfamily, a widely used marker for mesothelial differentiation. It is also found to be expressed in breast carcinoma. Breast carcinoma is the leading cause of cancer death in women and despite new approaches and advances, it is still difficult to predict the behaviour of the tumour and its prognosis. So there is a need and struggle to identify new markers for prognosis of breast cancer. The study is aimed at evaluating the frequency of Calretinin expression in breast carcinoma and assessing the characteristics of Calretinin positive tumours. Thirty mastectomy specimen of invasive breast carcinoma were analysed histopathologically and for immunohistochemical expression of ER, PR, HER2/neu and Calretinin. In this study 93.33% (28 cases) were of invasive carcinoma, NST and 6.67% were of other subtypes. Patients less than 40 years of age showed low CR expression and patients over 40 showed high CR expression (p = 0.22). Grade 3 tumours showed high CR, grades 1 and 2 showed low CR expression. Lymph node positive cases showed high CR and lymph node negative cases showed low CR. Tumours less than 5cms in size show low CR expression and those over 5cms showed high CR expression (p = 0.38). Negative ER, PR and HER2/neu showed high CR expression. CR expression was high in 54.5% of basal-like subtype and 66.7% of HER2-enriched.CR expression was low in 50% of luminal cases. High Calretinin expression was seen in grade 3, HER2-enriched and basal-like subtypes of breast cancer which may be of considerable prognostic significance.